1999
DOI: 10.1128/jvi.73.4.2667-2674.1999
|View full text |Cite
|
Sign up to set email alerts
|

Vif and the p55 Gag Polyprotein of Human Immunodeficiency Virus Type 1 Are Present in Colocalizing Membrane-Free Cytoplasmic Complexes

Abstract: The Vif protein of human immunodeficiency virus type 1 (HIV-1) is a potent regulator of viral infectivity. Current data posit that Vif functions late in replication to modulate assembly, budding, and/or maturation. Consistent with this model, earlier indirect immunofluorescence analyses of HIV-1-infected cells demonstrated that Vif and Gag colocalize to a substantial degree (J. H. M. Simon, R. A. M. Fouchier, T. E. Southerling, C. B. Guerra, C. K. Grant, and M. H. Malim, J. Virol. 71:5259–5267, 1997). Here, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
20
0
1

Year Published

1999
1999
2014
2014

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(24 citation statements)
references
References 61 publications
3
20
0
1
Order By: Relevance
“…Consistent with the model that Vif provides a critical function during virus production, confocal microscopy analyses of HIV-1-and feline immunodeficiency virus-infected cells have shown that there is substantial colocalization between Gag and Vif (24). Furthermore, we have recently demonstrated that p55 Gag and Vif derived from lysates of HIV-1-infected cells cofractionate in continuous density gradients in the presence of nonionic detergent (23). Importantly, however, coimmunoprecipitation experiments failed to provide evidence to support the idea that Vif and Gag stably interact with each other (23), a finding that appears to contrast with one recent report (2).…”
supporting
confidence: 80%
See 2 more Smart Citations
“…Consistent with the model that Vif provides a critical function during virus production, confocal microscopy analyses of HIV-1-and feline immunodeficiency virus-infected cells have shown that there is substantial colocalization between Gag and Vif (24). Furthermore, we have recently demonstrated that p55 Gag and Vif derived from lysates of HIV-1-infected cells cofractionate in continuous density gradients in the presence of nonionic detergent (23). Importantly, however, coimmunoprecipitation experiments failed to provide evidence to support the idea that Vif and Gag stably interact with each other (23), a finding that appears to contrast with one recent report (2).…”
supporting
confidence: 80%
“…Transient infection of H9 cells with HIV-1. Cells were transiently infected with HIV-1 carrying a wild-type or mutated vif gene as previously described (23). Specifically, initial high-titer stocks of pseudotyped viruses were transiently generated by transfection of 293T monolayers with the relevant pIIIB-based proviral vector and pHIT/G (28).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…By using a 5 -labelled (dT) 20 oligonucleotide as primer, we could directly visualize the synthesized products on a polyacrylamide gel. As shown in Figure 3(B), addition of increasing amounts of wild-type Vif (lanes [3][4][5][6] or of Vif N (lane 7-10) resulted in the stimulation of total DNA synthesis by HIV-1 RT, compared with control reactions without Vif (lanes 1 and 2). On the other hand, the Vif C mutant failed to stimulate HIV-1 RT activity.…”
Section: The C-terminal Domain Of Vif Is Required For Stimulation Of mentioning
confidence: 85%
“…The vif gene is conserved in almost all lentiviruses of primate and non-primate hosts, indicating an essential role for its product in the replication of these viruses [4]. The vif gene encodes the 23 kDa basic protein Vif, a substantial fraction of which is membrane-associated in virus-producing cells and co-localizes with the protein Gag [5,6]. Analysis of the reverse transcription process in Vif HIV-1 mutants in non-permissive cells showed a specific block in the synthesis of minusand plus-strand viral DNA products, resulting in an inability to produce full-length viral DNA genomes [7].…”
Section: Introductionmentioning
confidence: 99%